Sensitive biomarkers of alcoholism's effect on brain macrostructure: similarities and differences between France and the United States - Le Berre, Anne-Pascale; Pitel, Anne-Lise; Chanraud, Sandra; Beaunieux, Hélène; Eustache, Francis; Martinot, Jean-Luc; REYNAUD, Michel; Martelli, Catherine; Rohlfing, Torsten; Pfefferbaum, Adolf; Sullivan, Edith V. (Frontiers in Human Neuroscience, 2015)
Alcohol consumption patterns and recognition of health outcomes related to hazardous drinking vary widely internationally, raising the question whether these national differences are reflected in brain damage observed in alcoholism. This retrospective analysis assessed variability of alcoholism’s effects on brain cerebrospinal fluid (CSF) and white matter volumes between France and the United States (U.S.). MRI data from two French sites (Caen and Orsay) and a U.S. laboratory (SRI/Stanford University) were acquired on 1.5T imaging systems in 287 controls, 165 uncomplicated alcoholics (ALC), and 26 alcoholics with Korsakoff’s Syndrome (KS). All data were analyzed at the U.S. site using atlas-based parcellation. Results revealed graded CSF volume enlargement from ALC to KS and white matter volume deficits in KS only. In ALC from France but not the U.S., CSF and white matter volumes correlated with lifetime alcohol consumption, alcoholism duration, and length of sobriety. MRI highlighted CSF volume enlargement in both ALC and KS, serving as a basis for an ex vacuo process to explain correlated gray matter shrinkage. By contrast, MRI provided a sensitive in vivo biomarker of white matter volume shrinkage in KS only, suggesting a specific process sensitive to mechanisms contributing to Wernicke's encephalopathy, the precursor of KS. Identified structural brain abnormalities may provide biomarkers underlying alcoholism's heterogeneity in and among nations and suggest a substrate of gray matter tissue shrinkage. Proposed are hypotheses for national differences in interpreting whether the severity of sequelae observe a graded phenomenon or a continuum from uncomplicated alcoholism to alcoholism complicated by KS.